Synthesis of magnetic nanofibers using femtosecond laser material processing in air - Alubaidy, Mohammed-Amin (Springer, 2011)
In this study, we report formation of weblike fibrous nanostructure and nanoparticles of magnetic neodymium-iron-boron (NdFeB) via femtosecond laser radiation at MHz pulse repetition frequency in air at atmospheric pressure. Scanning electron microscopy (SEM) analysis revealed that the nanostructure is formed due to aggregation of polycrystalline nanoparticles of the respective constituent materials. The nanofibers diameter varies between 30 and 70 nm and they are mixed with nanoparticles. The effect of pulse to pulse separation rate on the size of the magnetic fibrous structure and the magnetic strength was reported. X-ray diffraction (XRD) analysis revealed metallic and oxide phases in the nanostructure. The growth of magnetic nanostructure is highly recommended for the applications of magnetic devices like biosensors and the results suggest that the pulsed-laser method is a promising technique for growing nanocrystalline magnetic nanofibers and nanoparticles for biomedical applications.